The Analysis of Accuracy in Translating Indonesian Texts into English by Grade Eleven Students of HKBP Lintong Nihuta Private High School in Explanatory Texts - Rohanna Sinambela; Bloner sinurat (Journal of Translation, Linguistics and Literature, 2024)
This research aims to show the level of translation accuracy of class XI students at HKBP Lintong Nihuta Private High School for the 2023/2024 academic year. In this research, there were several problematic phenomena that occurred during previous observations in class XI. where there are still many students who do not understand good translation techniques, which often results in errors in the translation results. This creates confusion among students about good translation, for example; Students don't know how to use grammar properly; student translate the sentence by word for word so, the meaning of the sentence is not conveyed properly. and students lack mastery of English vocabulary. The method used in this research is a qualitative descriptive method because it is based on phenomena that occur. The data source used in this research uses explanatory text taken from the Detik.com website. The procedural technique used is qualitative data analysis. There were 20 students who took part in carrying out the translation of this text. The findings obtained were none of the students that get the Highly accurate and there are only 6 (30%) students that get that accurate level, and 12 (60%) students for the less accurate and there are 2 (10%) students that gets the Inaccurate level. So, it can be concluded that students' level of accuracy is still at the level Less accurate.